Trainers' Performance in Entrepreneurship Class: Evidence from Lesson Planning of Non-Formal School in Lombok Timur - Muh Fahrurrozi; Mohzana Mohzana; Hary Murcahyanto; Hasan Basri (AL-ISHLAH: Jurnal Pendidikan, 2022)
Lesson planning constitutes the teacher's critical guide in successful learning activities. Because of its role, lesson planning is prioritised, not as a complement to the teaching administration. Therefore, this study investigates how the trainers' ability to design lesson planning with the learner's response to teaching performance in the classroom. Classroom action research is adopted as a research method implemented in non-formal schools; Bale Beleq Institute, Lombok Timur. Participants came from several representative villages from POKDARWIS (tourism care group). Some were active in the Karang Taruna of eleven people studying entrepreneurship under the sub-topic of products and markets. When processing data, three instruments were used; in-depth interviews, observation-participant, and document reviews. Findings show a positive relationship between the ability of trainers to design lesson planning and the performance of teaching trainers in the classroom. Successful indicators refer to the trainer's understanding of the constituent components of lesson planning and learners' opinions from open interviews after the learning. In addition, the better trainers' understanding of designing the lesson planning, the better implication toward learning output must be.